UKRAINIAN-LATVIAN COMPARATIVE STUDIES ON UNIVERSITY EDUCATION: COMMON EUROPEAN VALUES AND CURRENT CHALLENGES - Topuzov, Oleh; Malykhin, Oleksandr; Usca, Svetlana; Aristova, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Knowledge on universal values in general and common European values in particular and their influence on the process of providing university education to current and future generations may become a basis for building a cohesive world community. In that context, university education has an invaluable role to play. To live in peace and harmony for years to come, people should acknowledge and respect the diversity within the global society. This will be possible only if the content of higher education programmes in universities throughout Europe provides the next generations with insight into European and world culture and multiculturalism. This is most evident now when all the nations of the world have expressed their willingness to help each other in combating the Covid-19 pandemic placing the highest value on the person. In this regard, the article is aimed at investigating the problems Ukrainian and Latvian students face as a result of current challenges caused by the Covid-19 pandemic, providing some scientifically backgrounded ways of their overcoming and reducing their negative consequences. The problems whose essence was found out through conducting a web-based questionnaire were generalized by means of content analysis method. Research sample included 109 Latvian students and 98 Ukrainian students.